Institutional herding and its price impact: Evidence from the corporate bond market - Cai, Fang; Han, Song; Li, Dan; Li, Yi (Journal of Financial Economics, 2019)
We examine the extent to which institutional investors herd in the U.S. corporate bond market and the price impact of their herding behavior. We find that the level of institutional herding in corporate bonds is substantially higher than what is documented for equities, and that sell herding is much stronger and more persistent than buy herding. The price impact of herding is also highly asymmetric. While buy herding facilitates price discovery, sell herding causes transitory yet large price distortions. Such price destabilizing effect of sell herding is particularly pronounced for speculative-grade, small, and illiquid bonds, and during the financial crisis.